UN Convention on the Rights of the Child: Participation - Šimović, Ivan (International Children's Rights, 2024)
This chapter examines children’s participation rights as fundamental civil and political rights intended for children as sole holders, as envisaged by the Convention on the Rights of the Child. The contemporary perspective is that participation rights encompass the pivotal right of the child to express his or her views freely in all matters that affect him or her (Article 12) and other significant participation rights, such as the right to freedom of expression (Article 13), the right to freedom of thought, conscience and religion (Article 14), and the right to free association and peaceful assembly (Article 15). These rights are considered to be crucial for the “visibility” of the child and his or her respect as an active subject, not a passive object of law, because they contribute to proper participation of the child in his or her political, economic, social and cultural environment. This chapter thoroughly examines the scope, content, relevance and function of children’s procedural rights in theory and practice. It explains the interconnection and interdependence of these rights in their realisation, as well as the way the Convention imposes obligations on States Parties to respect, protect and promote these rights. This chapter aims to outline how States Parties to the Convention should create the national legal framework necessary to facilitate children’s effective enjoyment of all their participation rights, enabling them to participate in the decision-making process in all matters that affect them, considering their evolving capacities and the principle of the primary protection of their best interests.Keywords: children’s participation rights, the right to express views freely, the right to freedom of expression, the right to freedom of thought, conscience and religion, the right to free association and peaceful assembly, Committee on the Rights of the Child